The Influence of Competence, Knowledge and Attitudes of Midwives on The Implementation of Cervical Cancer Prevention Programs at Tangerang Hospital - Linda Mirawati; Cri Sajjana Prajna Wekadigunawan; Kemala Rita Wahidi (Syntax Corporation Indonesia, 2022)
According to the World Health Organization (WHO), cervical cancer is caused by infection with the HPV (Human Papilloma Virus) virus that does not heal for a long time. If the immune system is reduced, then this infection can be malignant (pathogenic) and cause cervical cancer. Prior to 1930, cervical cancer was still the main cause of death for women and cases dropped drastically since the introduction of the Pap smear screening technique by Papanicolauo in 1934, there had been a lot of progress so that in the United States and Western Europe, the incidence of cervical cancer had decreased.